Analysis of the Seawater Quality Index in the Marine Waters of Bontang City, East Kalimantan - Kurniawan, Burhan; Rizal, Samsul; Mandang, Idris; Pagoray, Henny; Sitorus, Saibun; Hamdhani, Hamdhani (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Seawater quality is a key factor in determining the health of coastal ecosystems and the sustainability of marine resources. Anthropogenic activities such as the discharge of industrial and domestic waste, marine transportation, and intensive fishing practices can influence the physical, chemical, and biological parameters of seawater. Research on seawater quality in the marine waters of Bontang City has been conducted, but remains very limited in number. This study aims to analyze the Seawater Quality Index (IKAL) in the marine waters of Bontang City. The analytical method employed refers to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 27 of 2021. The results indicate that the average Seawater Quality Index (IKAL) in Bontang City during the second semester of 2023 was 72.69, which is categorized as good condition.